Pre-Service Teachers' Perception and Beliefs of Readiness to Teach Mathematics - Clarissa Enid Rosas (Arizona State University, 2011)
This study explored pre-service teachersâ perceptions regarding their readiness to teach mathematical concepts and their preparation to integrate mathematical topics in instruction. Participants consisted of pre-service teachers who agreed to participate in a state-wide survey. For the purpose of this study, data was disaggregated into two groups: pre-service teachers who attended a private teacher education program and pre-service teachers who attended a public teacher education program. Results of this study indicate that pre-service teachers from both private and public colleges felt adequately prepared to teach mathematics and were indifferent in their perception of their ability to integrate mathematical concepts.